Remote learning: the impact of the COVID-19 pandemic on music therapy students' perceived skills and concerns regarding internships - Schmidt, Shealyn D., author; Knight, Andrew, advisor; LaGasse, Blythe, committee member; Graham, James, committee member (Colorado State University. Libraries, 2022)
The purpose of this study was to examine the self-perceived skills and concerns of music therapy (MT) undergraduate and graduate equivalency students, who studied in the United States during the COVID-19 pandemic. This study implemented a cross-sectional survey design, using Likert scale questions from Clements-Cortés's 2019 study about music therapy students' self-perceived skills and concerns regarding internship, published in the Journal of Music Therapy. The researcher used validation measures to condense the original survey from 53 to 25 questions. Participants were also asked to indicate the amount of remote learning (high, medium, or low), student level (graduate equivalency or undergrad) and their current internship status. A Qualtrics survey link was sent to students via music therapy student organizations' social media pages, and resulted in a sample of fifty-two student participants. Data were analyzed using descriptive statistics and a Kruskal Wallis H test with Bonferroni correction was used to determine significant differences between perception of skill or concerns and the amount of remote learning or student level (grad or undergrad). The highest self-perceived skill of UG participants was Professional Relationships and the lowest was Piano Improvisation. The highest self-perceived skill of GE students was Creative MT Technique Knowledge and Use and the lowest was Handling Stress. The highest self-perceived concern of UG was Making Spontaneous Adaptations and the lowest was Handling Session Unpredictability. The highest self-perceived concern of GE was Finances and the lowest was Handling Session Unpredictability. Results indicated that participants perceived benefits and drawbacks of remote learning. The amount of remote learning (high, medium, low) showed significant differences were found for perception of skills among high-remote internship students, and for skills and concerns among students with high in person internship and high-remote practicum categories. The majority of significant results were found in the high-remote practicum category. There were no significant differences found within the in-person practicum category. As compared with pre-internship undergraduate MT students in Clements-Cortés (2019) study, pre-interns in the current study rated themselves as more skilled on 9 of 12 items. However, post-interns in the current study rated themselves as less skilled on all 12 items. Pre-interns in the current study rated themselves as less concerned than pre-interns in Clements-Cortés (2019) study on 9 of 13 items. However, post-interns in the current study rated themselves as less concerned on all 13 items. In MT students' written responses about the impact of remote learning, the most frequently reported disadvantages included fewer in-person experiences and technological difficulties. The most frequent advantages reported included learning (specifically an increase in knowledge) and convenience. Individual perspectives appeared to impact whether certain elements of remote learning were seen as positive or negative thing. At present, the COVID-19 pandemic is ongoing and remote learning technology will likely continue to be used. Further research about the use of remote technology in music therapy education can help to gain insight on how to make the internship and profession more accessible for students.